Implementation of The Critical Thinking Skills Measurement Instrument Integrated with the Critical and Creative Thinking in Research-Based Learning Model - Mawardi Mawardi; Yohana Setiawan; Suhandi Astuti; Mawardi; Yohana Setiawan (Universitas Negeri Malang, 2027)
This study addresses the limited availability of critical thinking assessment instruments that comprehensively measure university students' competencies in higher education. Existing FRISCO-based instruments are constrained by suboptimal internal consistency, a predominant focus on cognitive dimensions, limited assessment of critical thinking dispositions, and potential subjectivity arising from inconsistent interpretation of assessment criteria. To overcome these limitations, the Critical Thinking Skills Measurement Instrument (CTSMI) integrated with the Critical and Creative Thinking Research-based Learning (CCTRbL) model was developed. This study aimed to examine the validity, effectiveness, implementation fidelity, and user acceptability of the integrated CTSMI. A mixed-methods approach combining a pre-experimental design and Collaborative Action Research (CAR) was employed, involving four lecturers and a hundred undergraduate students. Expert validation by specialists in psychology, linguistics, and educational evaluation produced mean scores of 77.0, 77.8, and 72.0, respectively, confirming the instrument's validity. Empirical testing yielded a Cronbach's alpha coefficient of 0.734, while Corrected Item–Total Correlation values demonstrated that all items met the validity criterion (r ≥ 0.30). Implementation of the CTSMI integrated with the CCTRbL model resulted in a mean critical thinking score of 68, indicating a high level of performance. The findings demonstrate that the CTSMI is a valid and reliable instrument for assessing and promoting university students' critical thinking skills. Furthermore, the instrument exhibited strong user acceptability and was implemented effectively, supporting its applicability as a comprehensive assessment tool for higher education learning environments.